Coumarin Derivative from the Unripe Fruit of Mengkudu (Morinda citrifolia Linn) and Cytotoxic Activity - Ferlinahayati, Ferlinahayati; Nisa, Sarifatun; Hermansyah, Hermansyah; Basir, Dasril (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2023)
A coumarin derivative namely scopoletin (7-hydroxy-6-methoxychromen-2-one) had been isolated from the methanol extract of unripe noni fruits (Morinda citrifolia Linn.). The extraction was conducted by maceration, continuing with separation and purification using several techniques of chromatography. The yellowish isolated compound showed a melting point at 200 – 202 °C. The compound structure was analyzed based on spectral data 1H-NMR, 13C-NMR, and NOE 1D. The inhibition of methanol extract of noni fruits and scopoletin against murine leukemia P388 cells using MTT assay showed IC50 were > 100 μg/mL and 65.69 μg/mL respectively. These showed that scopoletin was more cytotoxic than methanol extract but weaker than artonin E as a positive control IC50 0.48 μg/mL)